Beetroot red (betanin) inhibits vinyl carbamate‐ and benzo(a)pyrene‐induced lung tumorigenesis through apoptosis. Issue 9 (27th March 2012) - Zhang, Qi; Pan, Jing; Wang, Yian; Lubet, Ronald; You, Ming
Abstract Betanin, also called beetroot red, has been extensively used as a food colorant. In this study, the chemopreventive activity of betanin by oral consumption was investigated in two mouse lung tumor models. Vinyl carbamate (VC) and benzo(a)pyrene (B(a)P) were used to induce lung tumors, and female A/J mice were treated with betanin in drinking water. Betanin significantly decreased tumor multiplicity and tumor load induced by both carcinogens. Tumor multiplicity and tumor load were decreased by 20% and 39% in the VC lung model, and by 46% and 65% in the B(a)P lung model, respectively. Betanin reduced the number of CD31+ endothelial microvessels and increased the expression of caspase‐3, suggesting that the lung tumor inhibitory effects were through induction of apoptosis and inhibition of angiogenesis. Betanin also induced apoptosis through activated caspase‐3, ‐7, ‐9, and PARP in human lung cancer cell lines. Our data show that betanin significantly inhibits lung tumorigenesis in A/J mice and merits investigation as a chemopreventive agent for human lung cancer. © 2012 Wiley Periodicals, Inc.